Characterization of Phlebotomus papatasi peritrophins, and the role of PpPer1 in Leishmania major survival in its natural vector - Coutinho-Abreu, Iliano V.; Sharma, Narinder K.; Robles-Murguia, Maricela; Ramalho-Ortigão, Marcelo (My University, 2013)
The peritrophic matrix (PM) plays a key role in compartmentalization of the blood meal and as barrier to pathogens in many disease vectors. To establish an infection in sand flies, Leishmania must escape from the endoperitrophic space to prevent excretion with remnants of the blood meal digestion. In spite of the role played regarding Leishmania survival, little is known about sand fly PM molecular components and structural organization. We characterized three peritrophins (PpPer1, PpPer2, and PpPer3) from Phlebotomus papatasi. PpPer1 and PpPer2 display, respectively, four and one chitin-binding domains (CBDs). PpPer3 on the other hand has two CBDs, one mucin-like domain, and a putative domain with hallmarks of a CBD, but with changes in key amino acids. Temporal and spatial expression analyses show that PpPer1 is expressed specifically in the female midgut after blood feeding. PpPer2 and PpPer3 mRNAs were constitutively expressed in midgut and hindgut, with PpPer3 also being expressed in Malpighian tubules. PpPer2 was the only gene expressed in developmental stages. Interestingly, PpPer1 and PpPer3 expression are regulated by Le. major infection. Recombinant PpPer1, PpPer2 and PpPer3 were obtained and shown to display similar biochemical profiles as the native; we also show that PpPer1 and PpPer2 are able to bind chitin. Knockdown of PpPer1 led to a 44% reduction in protein, which in spite of producing an effect on the percentage of infected sand flies, resulted in a 39% increase of parasite load at 48 h. Our data suggest that PpPer1 is a component for the P. papatasi PM and likely involved in the PM role as barrier against Le. major infection.
Citation: Coutinho-Abreu IV, Sharma NK, Robles-Murguia M, Ramalho-Ortigao M (2013) Characterization of Phlebotomus papatasi Peritrophins, and the Role of PpPer1 in Leishmania major Survival in its Natural Vector. PLoS Negl Trop Dis 7(3): e2132. doi:10.1371/journal.pntd.0002132
Keywords: Peritrophic matrix; Disease vectors; Phlebotomus papatasi